Non-conventional metallographic replication alternatives: A comparative study - Briceño Roldan, Federico Braulio; Zavaleta Gutierrez, Nilthon Emerson; Ñique Gutierrez, Norberto Damián; Polo Briceño, Elmer Rolando; Sandoval Ochoa, Joel Johnny (LACCEI, 2025)
In industrial components subjected to high temperatures, it is crucial to evaluate the microstructural changes that occur during their service life to predict the remaining useful life without altering their operating condition. The non-destructive technique of metallographic replication constitutes an excellent alternative for its characterization. Three methods were compared to obtain metallographic replicas that allow observing the typical microstructural details in ferrous alloys. Commercial replicating materials of ethyl acetate on a reflective aluminum support (Transcopy brand), replicas with silicone rubber (RepliSet brand) and low-cost ASA 200 veiled roll ethyl acetate photographic film were selected. Metallographic replication was applied to ferrous alloys surface prepared by roughing, polishing, chemical and electrolytic etching. The microstructural details in each specimen and its respective replicas were evaluated by optical microscopy. The results indicate that metallographic replicas reveal most of the microstructural details obtained with conventional (destructive) metallographic inspection. Replicas made with ASA 200 frosted ethyl acetate photographic film exhibit excellent resolution for viewing microstructural details, with optical magnifications of up to 1000X in the samples studied; similar results were obtained with ethyl acetate replicas on reflective aluminum supports and with silicone rubber. However, silicone rubber replicas have limitations in revealing details in fine microstructures.